EFFICIENCY COMPARISON NON-OPTIMAL SYSTEM AND STABILIZATION SYSTEM WITH OPTIMIZED REGULATOR PARAMETERS - Блохін, Л. М.; Держак, С. В.; Білак, Н. В. (Proceedings of National Aviation University (archive), 2021)
The comparison of the efficiency of the suboptimal system and the stabilizer system with the optimized parameters of the controller under random influences on the control object is considered. Graphical dependences of estimates of efficiency of systems on the parameters essential for the decision of problems of synthesis are constructed.